IMPLEMENTASI APLIKASI MOBILE PERAWATAN KECANTIKAN KULIT WAJAH MENGGUNAKAN METODE SDLC - Desi Ana Dewi; Listiarini Edy Sudiati; Ninik Haryani (SOSCIED, 2022)
Along with the development of current technology, there are still some clinics that have not used advanced technology. One of them, MyTamara Clinic, which is located in the city of Pati. Such as carrying out consultations and reservations, patients must come directly to the clinic or make reservations by telephone. But this is not effective because patients who want to make reservations at the clinic are always full. In order to overcome these cases, it is necessary to develop a system that can overcome these problems. The system development that I use is SDLC (Application Development Life Cycle) in 5 sessions, namely Analysis, Design, Implementation, Testing, and Maintenance. This app uses Android Studio. This application design is supported by UML (Unified Modeling Language) program tools. This application can assist patients in finding information about the MyTamara clinic, and can help the performance of employees and doctors in providing services at the MyTamara clinic with online, easy, and fast methods.